Upwelling Increases Net Primary Production of Corals and Reef-Wide Gross Primary Production Along the Pacific Coast of Costa Rica - Stuhldreier, Ines; Sánchez-Noguera, Celeste; Roth, Florian; Cortés, Jorge; Rixen, Tim; Wild, Christian (Frontiers in Marine Science, 2015)
Photosynthetic production is a key ecosystem service provided by tropical coral reefs, but knowledge about the contribution of corals and other reef-associated organisms and the controlling environmental factors is scarce. Locations with occurrence of upwelling events can serve as in-situ laboratories to investigate the impact of environmental variability on production rates of reef-associated organisms. This study investigated individual and reef-wide net (Pn) and gross primary production (Pg) for the dominant autotrophic benthic organisms (hard corals Pocillopora spp., crustose coralline algae (CCA), turf algae, and the macroalga Caulerpa sertularioides) associated with a coral reef along the Pacific coast of Costa Rica. Oxygen fluxes by these organisms were measured at a weekly to monthly resolution over one year (May 2013 - April 2014) via in-situ chamber incubations. The influence of simultaneously measured environmental parameters (temperature, light, inorganic nutrient concentrations, dissolved and particulate organic matter concentrations) on Pn of the different taxa were tested via linear model fitting. Turf algae showed highest individual Pn and Pg rates per organism surface area (35 and 49 mmol O2 m-² h-1), followed by Pocillopora spp. (16 and 25 mmol O2 m-² h-1), CCA (9 and 15 mmol O2 m-² h-1) and C. sertularioides (8 and 11 mmol O2 m-² h-1). Under upwelling conditions (February – April 2014), Pn rates of all algal taxa remained relatively uniform despite high nutrient availability, Pn of corals increased by 70 %. On an ecosystem level, corals on average contributed 60 % of total Pn and Pg per reef area (73 and 98 mmol O2 m-² h-1, respectively) due to high benthic coverage, followed by turf algae (25 %). Under upwelling conditions, reef-wide Pg increased by >40 %, indicating acclimatization of local reef communities to upwelling conditions.